American Society of Nephrology Clinical Pathological Conference - Meyers, Kevin E. (American Society of Nephrology, 2014)
A 13-year-old girl presented with proteinuria and acute kidney failure. She was born at full term via cesarean delivery (due to nuchal cord), but there were no other prenatal or perinatal complications. In early childhood the patient had two hospitalizations at ages 4.5 and 9 years, respectively, the latter for pneumonia. She had no history of symptoms of kidney disease. She came to the hospital at age 12 years for routine bilateral molar extractions. She was treated with oral antibiotics and discharged after the procedure without complications. At age 13 years, 10 months after the molar extraction, she was seen by a pediatrician because of puffiness and increased BP. She had had respiratory symptoms 2 weeks before presentation. The pediatrician prescribed furosemide and amlodipine. A few days later, the patient returned to the pediatrician’s office because of hand, ankle, and facial swelling and malaise. The pediatrician recommended hospitalization and the patient was admitted at this time.